India inside : the emerging innovation challenge to the West - Kumar, Nirmalya; Puranam, Phanish (Boston, Mass. : Harvard Business Review Press, 2012)
From President Obama to Prime Minister Singh, Leaders worldwide now cite innovation as crucial to the future prospects of their respective nations and to global commerce in general. In India Inside, authors and respected London Business School professors Nirmalya Kumar and Phanish Puranam claim that the long-held monopoly on innovation by Western corporations is over--and that nations, policy makers, and organizations need to look East to a hidden movement that is changing how innovation happens. In India Inside, Kumar and Puranam deliver a wake-up call to thinkers and companies in the developed world, as well as to policy makers in India --Book Jacket.
Where are the Indian Googles, iPods, and Viagras? -- Globally segmented innovation: how multinational companies leverage Indian talent -- Outsourcing innovation: R&D services on demand -- Process innovation: an injection of intelligence -- Management innovation: the global delivery model -- Visible innovation: frugal engineering -- India's innovation challenge: overcoming institutional constraints -- The future of Indian innovation.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Technological innovations -- India; Diffusion of innovations -- India; New products -- India; Research, Industrial -- India; Innovationsmanagement; Technische Innovation; Innovations -- Inde; Innovations -- Diffusion -- Inde; Produits nouveaux -- Inde; Recherche industrielle -- Inde; Diffusion of innovations; New products; Research, Industrial; Technological innovations; BUSINESS & ECONOMICS / Industries / General; Indien; India; elektronické knihy; electronic books